Microstructure, Magnetic and Electrical Properties of La0.67(Sr1-Xbax)0.33 Mn1-Ytiyo3 - Zainuddin, Zalita (2009)
A study on the microstructure, magnetic and electrical properties of La0.67Sr0.33MnO3 substituted with Ba at Sr site and Ti at Mn site have been performed. Samples of La0.67(Sr1-xBax)0.33 Mn1-yTiyO3 (LSBMT) with x = 0.00, 0.25, 0.50, 0.75 and 1.00; and y = 0.00, 0.05, 0.10, 0.15, 0.20, 0.40 and 0.60 were prepared using solid state reaction method. Quantitative compositional percentage data of the elements results confirmed the expected La:Sr:Ba:Mn:Ti ratios for the prepared samples. X-ray Diffractometer (XRD) spectrum showed single phase compounds, except for samples with y = 0.60 which have La2Ti2O7 peaks. Sr substitution with Ba changed the rhombohedral R-3c structure to cubic Pm3m, however Mn substitution with Ti only increased the lattice parameters values, without changing the whole structure. Scanning Electron Microscope (SEM) images showed a few porous structured samples, with coarse and fine grains while the others showed large closely packed grains with clear shapes and grain boundaries. The magnetization studies showed that samples with y = 0.00 exhibited a transition from the ferromagnetic to the paramagnetic phase as temperature increased and the Curie temperature, TC decreased from 371 K to 341 K when x increased from 0.00 to 1.00. TC also decreased when y increased. Magnetization versus field patterns did not differ much with x composition. The ferromagnetic behaviour for 0.00 ≤ y ≤ 0.15 change to paramagnetic when y ³ 0.20. Resistivity versus temperature study showed that samples with y = 0.00 had metal-like behaviour. Nearly all samples with 0.00 < y < 0.20 showed metallic and semiconducting-like behaviour. LSBMT with y ³ 0.20 exhibited only semiconducting behaviour. The metal-insulator transition temperature, TP decreased with increment of x and/or y. At T < TP the resistivity curves can be fitted with the r = r0 + r2T2 relations. For T > Tp the curves can be fitted with the variable range hopping (VRH) model and small polaron hopping (SPH) model. The density of states at Fermi level, N(EF) values were between 1018 to 1022 eV-1cm-3. Polaron activation energy, Ep increased with y ranging from 47 meV to 210 meV. Magnetoresistance (MR) measurement showed an increment of the MR % when the magnetic field increased and temperature decreased. The maximum MR % was ~34 % for LSBMT with x = 0.00 and y = 0.15 at 100 K and 1.0 Tesla. Samples with y £ 0.10 showed low field magnetoresistance (LFMR) effect. At 1000 Hz LSBMT with x = 0.00, 0.25 and 0.75 exhibit a ferroelectric-paraelectric transition peak at 200 K, 250 K and 225 K respectively, with the highest e' value of 6.54 x 105 when x = 0.25, y = 0.20. The Nyquist plots of Z" versus Z' showed depressed semicircles contributed by the grain, grain boundary and/or electrode effect. Two relaxation processes occurred in the AC conductivity curve due to the grain and grain boundary. Materials with very high dielectric constant ~ 105 at 1000 kHz were successfully synthesized with x £ 0.75; y = 0.20 and all samples with y = 0.40. Samples with y = 0.40 have wide range of nearly frequency and temperature independent high dielectric constant. These samples are excellent for capacitors fabrication.